GAMBARAN KONSUMSI SARAPAN PAGI, STATUS GIZI DAN TINGKAT PRESTASI BELAJAR ANAK SD NEGERI 124400 PEMATANGSIANTAR - Cahaya Elisabet Rumapea; Etti Sudaryati; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Having breakfast is the important thing to do before starting an activity every day, it could contribute a nutrition about 15%-30% of daily needs. For the elementary student, having breakfast is important for physical growth and achievement increase in study. This study aims to look at the consumption of breakfast, nutritional status, and level of student achievement SDN 124400 Pematangsiantar. This study is a descriptive research with cross sectional study design. This study population was all of students SDN 124400 Pematangsiantar, there were 117 people. The Sampling technique is simple random sampling with sample were 54 people. This study was conducted from February to September 2016. Data was obtained by questionnaires to the students that were selected as respondents. Data analysis wa performed as univariate. The results of this study showed that 70% of all students of SDN 124400 Pematansiantar often do breakfast with a frequency was 6-7 times a week. Most of the students have donated breakfast to sufficent energy (55,6%), and protein (74,1%) in the category enough. Nutritional status based on BMI/U showed that majority of students are categorized as normal (64,8%). The level of student achievement is largely in good category ( 75,9%). Nutritional status based on the frequency of breakfast with often category largely into normal category, and nutritional status based on the contribution of energy and protein with sufficient category largely into normal category. Student achievement based on the frequency of breakfast with often category largely into good category and level of learning achievement based on the contribution of energy and protein in sufficient category largely into normal category. Consumption breakfast elementary school students based on the frequency of breakfast was good, but the nutritional adequacy breakfast on students are still largely lacking in nutitional status and level of learning achievement is lacking. For all the students are supposed to improve their breakfast habit and for all the parents to help their children in having breakfast. Keywords : Consumption of breakfast, nutritional status, academic achievement, elementary school student